Kerion in Adulthood: A Rare and Severe Complication of Tinea Capitis - Silva, Natércia; Marques, Daniela; Pereira, Olga (Gazeta Médica, 2021)
Tinea capitis is a fungal infection of the scalp that occurs mainly in children. In some cases, it may progress to a severe complication called kerion celsi. The latter most commonly affects children between five and ten years old and it is characterized by an intense immune response to the infection, with the development of an inflammatory plaque, pustules, crusts and sometimes suppuration. This article describes the case of a seventy-two-year-old woman with a history of a painful and itchy inflammatory lesion of the scalp, with several weeks of evolution and resistant to treatment with different antibiotics. After observation by Dermatology, the diagnosis of a kerion celsi was established. The patient started specific treatment, with great improvement of the lesion and associated symptoms. Therefore, we portray an unusual and severe presentation of tinea capitis, particularly when considering the patient’s age group.